Anthropometrics and ergonomics of the female elderly ablution area / Noorul Amalia Azahar and Mayamin Yuhaniz - Azahar, Noorul Amalia; Yuhaniz, Mayamin (2018)
In a mosque, the ablution area is one of the main facilities associated with the users in relation to their physical characteristics and actions. Most of the mosques in Malaysia are still lacking in consideration towards female elderly users in terms of their capabilities and abilities that relate to anthropometrics and ergonomics. There are several standard guidelines, yet they are still deficient for certain groups of people. As an architect or designer, one should realize the importance of having the supporting fixtures namely handrail and seating in such a wet area. However, do the existing mosques comply with the needs of the female elderly specifically in terms of the anthropometrics and ergonomics of the ablution units? Masjid Sultan Ahmad and Masjid Geliga, Kemaman,Terengganu are the selected mosques for this case study. A survey method was conducted in this study which employed the result of both a series of observations and questionnaires that had been distributed to 30 randomly selected female elderly respondents aged 60 years old and above. In general, this paper contains the comparison data between existing guidelines and existing ablution units' dimension and how they affect users' satisfaction towards the ablution units in regard to anthropometrics and ergonomics. It showed most of the respondents are satisfied with the dimension of existing components for the ablution units at both mosques.